(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
The security of data flow is a major concern for the public network that is the Internet. A data transmission security method called steganography conceals the message within a media container, like an image. Undoubtedly, the media cannot carry so much embedded data. Because the image edge area can withstand pixel value fluctuations better than the center, the edge area is used to accommodate additional message bits. In this study, the hybrid Canny-Log detector was compared with hybrid Canny-Prewitt detector by compress a grayscale images using the Huffman algorithm and hid them in the edges of other color images. This combined two-detector method provides a larger edge area for increased message payload while keeping hidden images unnoticeable. The hybrid Canny-LoG detector was achieved better results in embedding capacity (EC) in terms of the number of pixels available for hiding. Additionally, good results were obtained in quality metrics, such as the mean squared error (MSE) and peak signal-to-noise ratio (PSNR) for the stego image.